2019
DOI: 10.1111/1467-8578.12247
|View full text |Cite
|
Sign up to set email alerts
|

Educational practitioners’ perceptions of ADHD: a qualitative study of views of the home lives of children with ADHD in the UK

Abstract: There is little research exploring educational practitioners’ experiences of working with children with attention deficit/hyperactivity disorder (ADHD). The current study aimed to understand educational practitioners’ beliefs concerning the home lives of children with ADHD, and how they perceive that home lives affect children’s behaviour in school. Forty‐two practitioners from primary, secondary and pupil referral schools participated in focus groups or interviews. Thematic analysis was used to identify theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Thus, there is still a lack of more detailed insight into factors influencing the quality of the teacher-ADHD student relationship from the lived experience of teachers. Moreover, there is also a need to closely explore how teachers‘ personal beliefs about ADHD students are formed and how those beliefs affect teachers‘ relationship to ADHD students, as suggested, e.g., a qualitative study by Russell et al ( 2019 ).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is still a lack of more detailed insight into factors influencing the quality of the teacher-ADHD student relationship from the lived experience of teachers. Moreover, there is also a need to closely explore how teachers‘ personal beliefs about ADHD students are formed and how those beliefs affect teachers‘ relationship to ADHD students, as suggested, e.g., a qualitative study by Russell et al ( 2019 ).…”
Section: The Present Studymentioning
confidence: 99%
“…The main themes identified in those teachers’ beliefs were: communication, collaboration and support, satisfactions, ambivalences and concerns, and professional preparation inadequacies. Russell et al ( 2019 ) found that educational practitioners believe that the disruptive school behaviour of ADHD childrenare determined by the home lives of those children, which are characterized by inconsistency, social isolation and psychosocial adversities such as drug abuse or domestic violence.…”
Section: The Present Studymentioning
confidence: 99%
“…Τέλος, από τα ευρήματα της έρευνας διαφαίνεται, σχετικά με τους αιτιολογικούς παράγοντες που συνδέονται με τη ΔΕΠ-Υ, πως οι Έλληνες εκπαιδευτικοί αποδίδουν τις συγκεκριμένες δυσκολίες σε νευρολογικούς παράγοντες. Η συγκεκριμένη εκτίμηση συναντάται και στις απόψεις των εκπαιδευτικών διεθνώς σε ό,τι αφορά τη φύση και την αιτιολογία της ΔΕΠ-Υ (Russell et al, 2019). Έρευνες στη χώρα μας καταδεικνύουν την όλο και αυξανόμενη σύνδεση των συμπτωμάτων της ΔΕΠ-Υ, από την πλευρά των εμπλεκομένων στις εκπαιδευτικές διαδικασίες, με οργανικές δυσκολίες (Δουβαρά & Τσάτσου, 2012).…”
Section: συζήτησηunclassified
“…No single cause of ADHD has been found but it is thought that individuals may develop the disorder through a complex interaction of biological and environmental risk factors (Russell et al 2019;Thapar et al 2013). It is important to understand that risks do not necessarily lead to adverse effects but enable an understanding of the multiple factors that may contribute to a diagnosis.…”
Section: Introductionmentioning
confidence: 99%